H2O Heroes: adding value to an environmental education outreach programme through intergenerational learning. Issue 2 (3rd April 2023) - Gilleran Stephens, Caroline; Short, Angela; Linnane, Suzanne
Abstract : H2 O Heroes is an environmental education programme, which was piloted with primary school students aged 7–10 years in a rural community in Co. Cavan, Ireland. Environmental education is frequently aimed at children not just as an educational initiative but as a means of changing attitudes and behaviour. H2 O Heroes brings children on a fun interactive 3 h classroom-based tour of a water catchment, focusing on the link between human activity and water quality. The goal of H2 O Heroes is to inspire, inform and engage so that children become environmental ambassadors for water (H2 O) protection and conservation. This study is centred on adding long-term value to a short-duration science outreach programme by looking at how its reach and 'message' can be transmitted to a wider audience through the ripple effect of intergenerational learning. This small-scale study employed a mixed-methods approach taking advantage of both quantitative and qualitative research tools. Targeted feedback from children, parents and caregivers demonstrated the effectiveness of the programme in promoting both environmental awareness and intergenerational learning. Findings indicate that participation in the H2 O Heroes programme empowered children as agents of environmental change and successfully improved environmental awareness and effected behavioural change within their families.